Oscillatory Solutions of Neutral Equations with Polynomial Nonlinearities - Vasil G. Angelov; Dafinka Tz. Angelova (International Journal of Differential Equations)
Existence uniqueness of an oscillatory solution for nonlinear neutral equations by fixed point method is proved.